Do metabolic derangements in end‐stage polycystic kidney disease differ versus other primary kidney diseases?. Issue 1 (17th December 2017) - Jankowska, Magdalena; Qureshi, Abdul Rashid; Barany, Peter; Heimburger, Olof; Stenvinkel, Peter; Lindholm, Bengt
ABSTRACT: Aim: Autosomal dominant polycystic kidney disease (ADPKD), a systemic disorder caused by mutation in genes encoding polycystins, has been reported to lead to metabolic derangements including new‐onset diabetes mellitus after kidney transplantation. We analyzed markers of insulin resistance (IR), inflammation, nutritional status and insulin‐like growth factor‐1 (IGF‐1) in end‐stage renal disease (ESRD) patients with ADPKD and ESRD patients with other primary kidney diseases. Methods: In a post hoc cross‐sectional analysis in 254 non‐diabetic CKD 5 patients starting on dialysis, glucose metabolism (insulin, IGF‐1, homeostasis model assessment of IR, HOMA‐IR), inflammation (high sensitivity C‐reactive protein, interleukin‐6, and tumour necrosis factor), nutritional status, and bone mineral density (BMD), were assessed. Survival was recorded for median time of 28 months (IQR 15–48 months). Results: Neither indices of IR, nor IGF‐1, inflammatory status, nutritional status, or BMD were different in patients with ADPKD as compared to other aetiologies of ESRD. Kaplan–Meier curves showed better survival among the ADPKD group versus other aetiologies, even after an exclusion of diabetic patients. Conclusions: The ESRD phenotype did not differ in ADPKD versus other primary kidney diseases in terms of markers of IR, inflammation, and nutritional status. This argues against the proposition that ADPKD patients are more prone to develop metabolic derangements beyond those generally observed in advanced CKD. However, additional studies are warranted to further elucidate systemic metabolic aspects of ADPKD. Summary at a Glance: This cross‐sectional study does not support the hypothesis that ADPKD patients with end‐stage kidney disease have a greater risk of metabolic derangement.